Antibiotic Prescribing Regimen and Resistance Awareness Among Eastern Libyan Dentists - Al-gadhy, Ranya; Rabee , Asmaa (Libyan Journal of Dentistry, 2025)
Background: The frequent use of antibiotics in dentistry for prophylaxis and treatment has contributed to a significant global public health issue: antibiotic resistance. Aim: This research aims to evaluate the patterns in the prescription of antibiotics and their prophylactic usage in treating systemic conditions. Additionally, it investigates the awareness as well as adherence to guidelines for antibiotic prescription, as well as the awareness of antibiotic resistance among dentists with advanced degrees and postgraduate (AD) qualifications, and those with bachelor’s Degrees (BD) in the eastern region of Libya. Materials and Methods: This cross-sectional study employed a questionnaire to gather data from a representative sample of 130 Libyan dentists in the eastern region (including Benghazi, Almarj, Albayda, Derna and Tobruk cities). Results: Most of the antibiotics prescribed by dentists were amoxicillin with clavulanic acid followed by amoxicillin alone, and both participant groups were adherent to the recommendations for prescribing antibiotics with statistically significant variation between the two groups. Conclusion: This study revealed a tendency to overprescribe and utilize antibiotics for particular dental diseases. The majority of dentists were aware of resistance to antibiotics and adhering to the antibiotic prescription guidelines, the participants acknowledged the recommended use of antibiotics as a preventive strategy for systemic conditions.